The Digital Crowd: Social media, mob psychology and mental health impacts (Journal of Psychiatrists' Association of Nepal, 2025)
The world is witnessing an unprecedented wave of digitalization that is reshaping communication, social interaction and even mental health and the digital tools have become central to everyday life. Among these, social media stands out as the most transformative force, turning what were once local conversations into global debates. In South Asia, for instance, the rise of platforms such as Facebook, TikTok, Twitter has profoundly altered communication patterns.